Integrating Postmodernism and Artificial Intelligence: The Emergence of English Language Philosophy in Digital Learning and Communication Paradigms: The Revolution of Learning Paradigms: Decentralizing English Language Teaching Through Artificial Intelligence - A N Iftitah; ST. Nurhayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the emergence of English philosophy mindsets in postmodern learning situations and changes in the way of communication in the Artificial Intelligence (AI) era. This research focuses on the role of language as a tool to deconstruct meaning, shows that meaning is relative, and allows for a variety of interpretations. This study explains how English, as a widely spoken global language, helped transform traditional ways of communication into a postmodern model supported by digital technology. The method used is qualitative by systematically collecting and analyzing various latest sources. This study seeks the pattern of experience from three main topics: deconstructing meaning, relativity of meaning, and the influence of AI on postmodern learning practices. The results show that English functions as an ever-changing mindset, is able to construct meaning through AI, blurs the boundaries between real life and hyperreality worlds, and triggers cultural resistance in the context of learning. The uniqueness of this research can be seen from the combination of a postmodern perspective and AI innovation, which provides a new understanding of how language develops in the digital environment. In a practical context, these findings help in developing an educational framework by increasing awareness of the illusions generated by AI, while theoretically, this research contributes to discussions on the philosophy of language and communication, as well as encouraging the formation of more inclusive and equitable learning models in the era of digital globalization.